2004
DOI: 10.1017/s0022029904000019
|View full text |Cite
|
Sign up to set email alerts
|

Influence of intramammary infection and non-infection factors on somatic cell counts in dairy goats

Abstract: A total of 1304 goat udder halves were sampled monthly during an entire lactation (6262 samples) with the aim of identifying factors affecting milk somatic cell count (SCC). Bacteriological analyses for identification of mastitis pathogens were carried out on all samples and SCC was also determined. All animals were examined for infection by caprine arthritis-encephalitis virus (CAEV) using a commercial ELISA test kit. Results obtained were arranged in two databases (whole-lactation average half-udder database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
1
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 21 publications
5
40
1
6
Order By: Relevance
“…Despite the above, Luengo et al (2004) confirmed that there is no significant interaction between the CAEV virus and the infection status of the mammary gland with respect to the SCC. This would explain a priori the worsening of the production records of seropositive goats, even more evident in elder goats (Martinez, 2000).…”
Section: Effect Of Caprine Arthritis Encephalitis Virusmentioning
confidence: 61%
See 1 more Smart Citation
“…Despite the above, Luengo et al (2004) confirmed that there is no significant interaction between the CAEV virus and the infection status of the mammary gland with respect to the SCC. This would explain a priori the worsening of the production records of seropositive goats, even more evident in elder goats (Martinez, 2000).…”
Section: Effect Of Caprine Arthritis Encephalitis Virusmentioning
confidence: 61%
“…This can be attributed to a longer exposure of the older animals to pathogens compared to younger animals, and to chronic infections established during the previous lactation and not completely eliminated during the dry period, rather than to a higher infection rate in older animals (Sánchez-Rodríguez et al, 2008;Marogna et al, 2012). However, Luengo et al (2004) showed that, considering only the glands with IMI, SCC is not higher in older animals. Test properties of composite SCC for detecting both MP and mP have been found to be strongly dependent on parity, with increasing parity yielding higher sensitivity and markedly lower specificity (Koop et al, 2011).…”
Section: Number Of Lactationmentioning
confidence: 85%
“…Ptak and Schaeffer [28], in dairy cows, and ElSaied et al [29], in dairy sheep, noted that adjustment for herd test date reduced the residual variance considerably, indicating the importance of taking into account effects specific to the day of test within each herd. Nevertheless, the main purpose of both ANOVAs was to study the significance of SCC and productive variables; the other factors of variation have been analyzed previously [4,6,19].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, several authors reported decreased fat content associated to high levels of SCC [7] while others did not find differences in fat content according to SCC level [15,16] or infection status [17][18][19] in small ruminants. In other studies, however, higher fat concentration was found in infected glands than in uninfected ones [20] or related to high levels of SCC [6].…”
Section: Introductionmentioning
confidence: 99%
“…The SCC has been widely used to assess the inflammatory status of the mammary glands of goats and sheep. LUENGO et al (2004) noted that multiple births and short-duration lactation were associated with an elevated SCC in milk. SOUZA et al (2012) provided a list of several factors that can affect the SCC of uninfected goats, such as: lactation stage; seasonality; milk production; numbers of kids; milking frequency and the use of machine milking or hand milking.…”
Section: Bc Cmt ------------------------------------------Scc--------mentioning
confidence: 99%